Analisis Kluster Perkembangan Bank Perkreditan Rakyat Syariah (BPRS) di Pulau Jawa - Husein, M. Fakhri (UIN Sunan Kalijaga, 2015)
There is little empirical evidence about the concentration of sharia rural credit bank’s development in Indonesia. This research is aimed to investigate about the development of sharia rural credit bank, whether is concentrated in the certain cities (as a center of economic growth) or in municipal areas. This research also explores the cluster of sharia rural development bank by using income growth, market share growth and asset growth variables. By analysing 68 sharia rural credit bank (BPRS) in 32 cities and municipals, this research found several interesting facts. First, there is no difference between cities and municipal in Java in terms of income growth, market share growth and asset growth. Second, there are two clusters of BPRS in terms of income growth, market share growth and asset growth variables. This research can be benefited by government and regulators to design and implement the sharia bank development strategy.